Religion and muslim women: trajectories of empowerment - Huq, Samia; Khondaker, Sahida Islam (BRAC University, 2011)
The report is based on a two‐year research project in which we looked at women’s everyday engagement with religion. We aimed to gain insights into how women conceptualize religion, the norms and concepts through which they understand what it means to be religious and the manner in which these concepts and ideals are brought to bear on the construction of the feminine self. The research focused on three arenas of women’s understanding of themselves as women and Muslim. These arenas are purdah, sexuality ‐ by which we mean male female relations ‐ and freedom and rights. From the research findings we argue that women have moved towards a textually‐based learning and interpretation of Islam, as opposed to engaging with Islam as a form of knowledge passed down from earlier generations. We also found that, in line with the need to “authenticate” beliefs, women express much respect for taleem ‐ spaces where women congregate to learn about the Quran and other exegetical material as well as ideal Islamic comportment. From the findings we argue that the role of religion in women’s lives cannot be understood through the binary of religious/conservative versus secular/liberal. Rather, by exploring the norms through which women understand religion and deploy corporeal as well as noncorporeal capacities to engage with those norms in “living” Islam we can shed light on greater nuances that under gird religious engagement. We then turn our attention to the negotiations theses nuances represent and how they open up questions about the “contentious” relationship between women, religion, agency and empowerment.